ANALISIS WACANA KRITIS MODEL VAN DIJK TERHADAP ISU “INDONESIA GELAP” DALAM PEMBERITAAN NARASI TEMPO - Chintia Simanjuntak; Amelia Malau; Rizky Azasya; Ningsih Febrina Simanungkalit (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study analyzes the narrative in Tempo's coverage of the "Indonesia Gelap" issue using Teun A. van Dijk’s Critical Discourse Analysis theory. The purpose of this research is to reveal how media discourse shapes representations of national conditions depicted through uncertainty, injustice, and weak legal supremacy. This study employs a descriptive-analytical qualitative approach, using primary data consisting of narratives in Tempo's news reports, complemented by a review of relevant literature. The analysis is conducted on three levels—macrostructure, superstructure, and microstructure—which shows that the news coverage highlights public dissatisfaction and the success of protest actions, while the government strives to shift the narrative toward national optimism and progress. The results of this study indicate that the language strategies used not only reflect the underlying ideology and power relations but also serve as a tool to shape public opinion. It is expected that this research will contribute to the development of Critical Discourse Analysis theory and deepen the understanding of the role of media in constructing socio-political realities.